Analisis Pengaruh Kualitas Jasa terhadap Kepuasan pada Industri Pendidikan di Yogyakarta - Munjiati Munawaroh (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
This research evaluates the effect of quality service on customer satisfaction in program studies of uni¬versity that are granted with accreditation rate either A or B from Badan Akreditasi Nasional. It also attempts to evaluate different quality service from program studies of university that are granted with accreditation rate either A or B, and to evaluate different quality service from program studies of university that are granted with accredita¬tion in same rated. Quality service is measured with SERVQUAL in five dimensions: reliability, responsiveness, assurance, empathy and tangibles. The results show that customer satisfaction is affected by assurance, tangibles and reliability dimension. It also show that quality service is not different in program studies of university that are granted with accreditation rate ei¬ther A or B in reliability, responsiveness, tangible and empathy dimension. The different quality services from program studies of university that are granted with accreditation rate either A or B is on assurance dimension. In program studies with same grant show that although they have accreditation rate A, they have different quality in five dimension, and in program studies that are granted with accreditation rate B, they have different quality in responsiveness, assurance and tangible dimension, but there are not different in empathy dimension.Key word: quality service, reliability, responsiveness, assurance, and empathy tangibles, Badan Akreditasi Nasional